1986
DOI: 10.1590/s0101-81751986000300001
|View full text |Cite
|
Sign up to set email alerts
|

Uso de redes de espera no estudo de ritmos circadianos de algumas espécies de peixes nos lagos de várzea do rio Solimões

Abstract: Rhythmic activity patterns are demonstrated for 15 species of fish in várzea lakes of the Solimões river by analyzing catch per hour-of-day INTRODUÇÃORitmos diários já foram observados em muitas espécies, relacionados a mudanças dclicas de diversos fatores ambientais. Essa alteração diária do comportamento da espécie é associada a sua estratégia de sobrevivência, que apresenta vantagens adaptativas em possuir a capacidade de "antever" e de se preparar para as mudanças ambientais previsrveis (Schwassmann, 1980)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
3
Order By: Relevance
“…Several investigators have observed that piscivores ingest prey smaller than one-third of their own length (Goulding et al, 1988;MachadoAllison, 1990;Almeida et al, 1997). However, this is not a rule, since the traíra Hoplias malabaricus, as reported in a number of studies, can ingest fish nearly its own length (Barthem, 1987;Winemiller, 1989;Almeida, 1994;Loureiro & Hahn, 1996). In the present study, the largest prey recorded was a specimen of Crenicichla niederleinii 9.5 cm long, eaten by an individual 23.3 cm long.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several investigators have observed that piscivores ingest prey smaller than one-third of their own length (Goulding et al, 1988;MachadoAllison, 1990;Almeida et al, 1997). However, this is not a rule, since the traíra Hoplias malabaricus, as reported in a number of studies, can ingest fish nearly its own length (Barthem, 1987;Winemiller, 1989;Almeida, 1994;Loureiro & Hahn, 1996). In the present study, the largest prey recorded was a specimen of Crenicichla niederleinii 9.5 cm long, eaten by an individual 23.3 cm long.…”
Section: Discussionmentioning
confidence: 98%
“…Studies on the feeding of A. lacustris are limited to those of Catella & Torres (1984) in Três Marias Reservoir, State of Minas Gerais; Mesquiatti (1995) in an oxbow lake of the Mogi-Guaçu River, State of São Paulo; and Almeida et al (1997) in the floodplain of the Upper Paraná River, State of Paraná. Trophic studies of large ichthyofaunistic communities have made brief reference to this species or others of the same genus (Barthem, 1987;Meschiatti, 1995;Benneman, 1996;Resende et al, 1996;Hahn et al, 1997). This paper describes the diet of A. lacustris in the area influenced by Itaipu Reservoir, the spacial and annual variations of the diet, its degree of overlap and the relationships between predator and prey sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences of results could have been determined by the influence of the food availability in the environments on the daily rhythms of feeding activity of fishes (BARTHEM, 1987). HAHN et al (1997) suggested that fishes that adopt a visual method of capturing organisms exhibit high feeding activity during the daylight.…”
Section: Discussionmentioning
confidence: 99%
“…They showed a negative relationship with transparency and a positive one with bauxite tailings. These species are active during twilight and at night (Barthem, 1987;Halboth, 1995), and are bottom inhabitants (Lin, 2003) with elaborate systems of sound production and requirements and a welldeveloped lateral line (Moyle & Cech, 1988). Thus, low transparency limits neither their distribution nor, probably, their foraging abilities; they are more abundant in turbid waters, as also observed by Rodrı´guez & Lewis (1997).…”
Section: Wl · Intermediate Area' Cpue (N)mentioning
confidence: 99%